Inferior outcomes for black children with high risk acute lymphoblastic leukemia and the impact of socioeconomic variables. Issue 2 (21st September 2016) - Walsh, Alexandra; Chewning, Joseph; Li, Xuelin; Dai, Chen; Whelan, Kimberly; Madan‐Swain, Avi; Waterbor, John; Baskin, Monica L.; Goldman, Frederick D.
Abstract: Background: While significant improvements have been made for children with acute lymphoblastic leukemia (ALL) in the United States over the past 20 years, black patients continue to have inferior outcomes. The full impact of socioeconomic variables on outcomes in this minority population is not entirely understood. Procedure: Disease characteristics, demographic, and socioeconomic status (SES) variables were collected on black (n = 44) and white (n = 178) patients diagnosed at the University of Alabama at Birmingham. Cox proportional hazard regression was used to evaluate the influence of SES and insurance status on survival. Results: As a cohort, 5‐year overall survival (OS) was 87% (82–91%), with a median follow‐up of 99 months. In univariable analysis, black race was not significantly associated with a higher risk of death or relapse and death. White and black patients with standard‐risk leukemia had excellent outcomes, with 97% (91–99%) and 96% (75–99%) 5‐year OS, respectively. In contrast, for high‐risk disease, white patients had a statistically significant improved 5‐year OS rates compared with black patients (79% [68–87%] vs. 52% [28–72%]). Black children were more likely to have public insurance, and, in multivariable analysis, this was associated with a trend toward an improved outcome. Black patients also had poorer census tract–level SES parameters, but these variables were not associated with survival. Conclusion: Our study demonstrates significantly inferior outcomes for black children with high‐risk leukemia. These outcome disparities were not related to SES variables, including poverty or private insurance coverage, suggesting the involvement of other factors and highlighting the need for a prospective investigative analysis.